Pengelolaan Pembelajaran Ilmu Tajwid Melalui Media Audio Visual - Hambali Hambali; Fathor Rozi; Nor Farida (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
This study aims to analyze and study the management of Tajweed learning through audio-visual media. This type of research is a method of qualitative case study type. The data collection techniques used in this study were observation, interview, and documentation. Data analysis using display data, data reduction, and conclusions. The results showed the management of tajwid learning through audio-visual media at TPQ Al-Muhajirin through the selection of tajwid learning materials, audio-visual-based tajwid implementation design, group daily tests, independent daily tests, and evaluations. The implication is that students are more eager to participate in tajwid learning and need training for teachers who have not mastered the technology. The implication of using audio-visual media makes it easier for students and teachers in the implementation of tajwid science learning.